Branding Pendidikan Vokasi Pariwisata: Perspektif Stakeholder Industri di Sulawesi Selatan - Arifin, Muhammad; Masatip, Anwari; Salim, Muhammad Arfin Muhammad; Eppang, Buntu Marannu; Badollahi, Muhammad Zainuddin (Universitas Negeri Makassar, 2021)
The literature on branding of educational institutions is still under development, so far there has been no research showing university branding. Research that has quantitative variations that have branding with other variables in the context of business organizations. This study aims to explore the formation of branding in vocational higher education institutions in the tourism sector. Data were taken using Focus Group Discussion and interviews from tourism stakeholders. This study uses thematic analysis, namely open coding and axial coding. The results show that there are main attributes in the formation of branding, namely identity, alumni, management aspects, quality of human resources and products and competitiveness. With the formation of these branding attributes, this research contributes to the measurement of tourism vocational education branding